Experimental and Computational Investigation of the 1, 3‐Dipolar Cycloaddition of the Ynamide tert‐Butyl N‐Ethynyl‐N‐phenylcarbamate with C‐Carboxymethyl‐N‐phenylnitrilimine. Issue 36 (30th October 2013) - González, Pedro Blas; Chandanshive, Jay Zumbar; Fochi, Mariafrancesca; Bonini, Bianca Flavia; Mazzanti, Andrea; Bernardi, Luca; Locatelli, Erica; Caruana, Lorenzo; Monasterolo, Claudio; Comes Franchini, Mauro
Abstract: The reactivity of the ynamide tert ‐butyl N ‐ethynyl‐ N ‐phenylcarbamate (1 ) in the 1, 3‐dipolar cycloaddition (1, 3‐DC) with C ‐carboxymethyl‐ N ‐phenylnitrilimine was investigated. This [3+2] cycloaddition affords the 5‐amino pyrazole as a single regioisomer. The obtained cycloadduct has been activated at the 4‐position of the pyrazole ring through bromination and subsequently coupled with a phenyl group under Pd catalysis. A detailed computational study has been performed to fully explain the complete regioselectivity observed. Abstract : The 1, 3‐dipolar cycloaddition (1, 3‐DC) of the ynamide tert ‐butyl N ‐ethynyl‐ N ‐phenylcarbamate with C ‐carboxymethyl‐ N ‐phenylnitrilimine affords the 5‐aminopyrazole as a single regioisomer. The activation of C‐4 through bromination followed by catalytic coupling with a Pd catalyst yields a tetrasubstituted pyrazole. A detailed computational study fully explains the regioselectivity.